The Plant Growth-Promoting Fungus MF23 (Mycena sp.) Increases Production of Dendrobium officinale (Orchidaceae) by Affecting Nitrogen Uptake and NH4+ Assimilation - Shan, Tingting; Zhou, Lisi; Li, Bing; Chen, Xiaomei; Guo, Shunxing; Wang, Airong; Tian, Lixia; Liu, Jingting (Frontiers in Plant Science, 2021)
Dendrobium officinale Kimura et Migo is a traditional and scarce medicinal orchid in China. Mycorrhizal fungi could supply nitrogen (N) to orchids for seed germination and seedling recruitment. However, the N transport mechanism between orchids and mycorrhiza is poorly understand. Early studies found that fungus MF23 (Mycena sp.) could promote the growth of D. officinale. To better dissect the molecular interactions involved in N transport between D. officinale and MF23, transcriptome and metabolome analyses were conducted on conventional and mycorrhizal cultivations of D. officinale. Moreover, validation tests were carried out in the greenhouse to measure net fluxes of NO3- and NH4+ of roots by a non-invasive micro-test technology (NMT), determine N assimilation enzyme activity by the enzyme linked immune sorbent assay (ELISA), and analyze the expression level of differentially expressed genes (DEGs) of N transporters and DEGs involved in N metabolism by RT-qPCR. Combined transcriptome and metabolome analyses showed that MF23 may influence N metabolism in D. officinale. The expression of DoNAR2.1 (nitrate transporter-activating protein), DoAMT11 (ammonium transporter), DoATFs (amino acid transporters), DoOPTs (oligopeptide transporters), and DoGDHs (glutamate dehydrogenases) in symbiotic D. officinale were up-regulated. NMT results showed a preference for NH4+ in D. officinale and indicated that MF23 could promote the uptake of NO3- and NH4+, especially for NH4+. ELISA results showed that MF23 could increase the activity of glutamine synthetase (GS) and glutamate dehydrogenase (GDH). This study suggested that MF23 increases the production of D. officinale by affecting N uptake and NH4+ assimilation capacity.